Empat Dimensi Keadilan Organisasional Yang Dipersepsikan Oleh Karyawan Terhadap Kepuasan Kerja - Sitti Marijam Thawil; Mohammad Anwar (Oikonomia: Jurnal Manajemen, 2021)
Purpose To examine the effect of the four dimensions of organizational justice on job satisfaction and to provide support that the four dimensions constitute different constructs is the aim of this study. Methodology 504 employees from two companies in Jakarta constitute the study population. Sampling technique with probability simple random sampling. The analysis technique used is multiple linear regression with SPSS 26. Findings Interpersonal justice has a negative and significant effect on job satisfaction and informational justice has a significant positive effect on employee job satisfaction. Suggestion Companies need to be careful in applying interpersonal justice because the effect can reduce employee job satisfaction. Companies should focus on providing a sense of informational justice if they want to increase employee job satisfaction. Future research needs to examine more deeply the antecedents, influence, mediation or moderation on interpersonal justice.